Applying quantitative methods to conservation planning : Population dynamics of the Eurasian otter in Ireland - Ó Néill, Lughaidh (Trinity College (Dublin, Ireland). Department of Zoology, 2008)
As appears typical in the field of conservation biology, the current study has parallel aims. The first is to improve both the limited toolbox and the biological information available for the conservation of a vulnerable species. The second is to compare and contrast the integrative, systematic and objective approach idealised by conservation biology with the traditional simplistic, or even ad hoc, approaches to conservation that persist for economically unimportant taxa. This thesis involves the gathering of information on the basic biology of otters and its synthesis into a logical modelling framework relating otter populations to the Irish landscape so as to optimise conservation measures. The thesis is presented as a series of published papers and manuscripts. Otters have been extremely difficult to capture and mark efficiently and humanely and research on some aspects of their biology was impeded as a consequence. I present and evaluate a novel trapping technique involving Global System for Mobile communication (GSM) trap alarms coupled with padded leghold traps. The trapping method was highly efficient compared with the most popular trap currently in use. Stress and trauma were minimised by removing animals from their traps within a matter of minutes.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin